2017
DOI: 10.1021/acs.jpcc.7b03311
|View full text |Cite
|
Sign up to set email alerts
|

Organic–Inorganic Halide Perovskite Formation: In Situ Dissociation of Cation Halide and Metal Halide Complexes during Crystal Formation

Abstract: Organic−inorganic halide perovskites have shown great promise as photovoltaic materials that bridge the gap between facile and low-cost fabrication and exceptional solar cell performance. Manipulation of the stoichiometry and chemistry of the precursors is among the main techniques for controlling the structural properties of perovskite layer. Herein we report that when a precursor solution containing excess cation halides (CH 3 NH 3 I) is utilized for perovskite formation, in situ dissociation of cations (CH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…When the MAI molecule reacts with PbI 2 and perovskite forms, almost all MAI peaks are shifted to other frequencies because of the change in the force constant of the bonds. The absorption peaks at 2961 and 1404 cm −1 are an asymmetric stretch and an asymmetric bend of CH 3 of MAI 14 , respectively. Also, the broad peak at 3095 cm −1 is related to the symmetric and asymmetric stretching modes of NH 3 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…When the MAI molecule reacts with PbI 2 and perovskite forms, almost all MAI peaks are shifted to other frequencies because of the change in the force constant of the bonds. The absorption peaks at 2961 and 1404 cm −1 are an asymmetric stretch and an asymmetric bend of CH 3 of MAI 14 , respectively. Also, the broad peak at 3095 cm −1 is related to the symmetric and asymmetric stretching modes of NH 3 .…”
Section: Resultsmentioning
confidence: 98%
“…It is known that the degradation and lifetime of a device are strongly dependent on all its components, fabrication process, and storing conditions 7,8 . In the case of the complete device degradation, several reasons are expressed for perovskite solar cell degradation such as the degradation of each device component 9,10 , the UV irradiation, chemical reaction between the perovskite layer and metal contacts, water molecules diffusion 1114 , and the surface and grain boundaries defects 15 . These defects originate from the low thermal stability, or low formation energy of perovskite materials that cause instability issues, comprising ion migration and associated current hysteresis that lead to the degradation of the device 15 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that other possible products of the decomposition of perovskite CH 3 NH 3 PbI 3 , except for the phase of PbI 2 , are CH 3 NH 2 and HI [42, 43]. Authors [44] have been shown that in the Fourier-transform infrared spectroscopy (FTIR) spectra of the products, there are bands indicating the presence of a C-I bond. Therefore, the reaction of the decomposition of organic-inorganic perovskite can be written as:…”
Section: Resultsmentioning
confidence: 99%
“…4c). Intermediate phases (CH 3 NH 3 ) 3 PbI 5 and (CH 3 NH 3 ) 2 PbI 4 were described in [44, 45]. With the increasing of the temperature of heat treatment up to 170 °C, a single-phase perovskite structure is formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation